The '2002 Peace Process' in the Sri Lankan media : comparing Sinhalese, Tamil and English editorial discourse in the national newspapers - Fernando, Theodore (Irish School of Ecumenics, 2007)
This case study analyses how three widely read national daily newspapers in Sri Lanka presented and framed the origins and ongoing development of the Norwegian-sponsored 2002 “Peace process” between the Sri Lankan government and LTTE (Liberation Tigers of Tamil Eelam) during the sixteen-month time period of December 2001 to March 2003.
Keywords: Ecumenics, Ph.D.; Ph.D. Trinity College Dublin